Investigation Study of Cephalexin Capsule Content from Different Drug Companies Available in the Iraqi Pharmaceutical Market - Ekhlass T Soore; Najib Al Sabea (Universitas Muhammadiyah Sidoarjo, 2024)
This study aimed to evaluate the cephalexin content in different capsule formulations from various pharmaceutical companies in the Iraqi market, ensuring medication safety and efficacy. Utilizing computerized High-Performance Liquid Chromatography (HPLC), we analyzed the cephalexin (500 mg) capsules, employing a calibration curve plotted with varying concentrations of external standard cephalexin USP. The purity of cephalexin was further verified through U.V. and I.R. studies. Our quantitative analysis focused on determining the active ingredient's weight based on the area under the peak. The results affirmed that all samples were within the 90%-120% range permitted by the USP 2007 standards, with recoveries approximating 100%, indicating remarkable accuracy and precision. Interestingly, BRULEXIN brand demonstrated the closest recovery to 100%. These findings suggest the effectiveness of HPLC as a rapid, accurate, and sensitive method for pharmaceutical analysis, not only for cephalexin but potentially for other medications as well, highlighting its suitability for routine quality control in the pharmaceutical industry. Highlights : All cephalexin capsule samples met the USP 2007 standard, indicating consistent quality in the Iraqi pharmaceutical market. High accuracy and precision of HPLC in quantifying active ingredients highlight its potential for broader pharmaceutical applications. BRULEXIN brand showed the closest to 100% recovery, underscoring the variability among different manufacturers. Keywords : Cephalexin Capsules, HPLC Analysis, Pharmaceutical Quality Control, Iraqi Market, Drug Purity